Методика исследования природы проектирования систем - Сорудейкин, К. А. (ХНУРЭ, 2008)
Main problems of Software Engineering appear as a result of incompatibilities. For example, the quality of organization of production process depends on correspondence with existent resources and on equivalence of comprehension of project goals by all members of a team. Software Design is another example. Its successfulness rides on architecture’s conformity with project’s concepts. This is a point of great nicety. All elements should make a single space of interactions. And if the laws of such space are imperfect missequencing comes and the concept of a software system fails. We must do our best for this not to have happened. To that end having a subtle perception of systems structures is essential. Such knowledge can be based only on a fresh approach to the logical law.
Keywords: природа проектирования систем